Retrospective clinicopathological analysis of scar endometriosis and its surgical management - Duraisamy, Kavitha Yogini; Balasubramaniam, Devi; Ravi, Karthikha; Subramaniam, Aravinth (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Scar endometriosis is a rare form of extrapelvic endometriosis. It is defined as presence of endometrial glands and stroma in the abdominal wall. They have a variable clinical presentation and present to various doctors. Abdominal mass along with cyclical pain is pathognomic of scar endometriosis. Objective was to analyse the clinical presentation and surgical outcomes of scar endometriosis. Methods: It was a retrospective observational study. We have collected records of 28 patients of scar endometriosis managed at GEM Hospital over a period of 3 years. Patients demographic features, previous surgery, clinical findings, surgical findings, association with pelvic endometriosis as noted on diagnostic laparoscopy, need for mesh, recurrence rate on follow up were noted. Results: Mean age of patients was 32.1 years. History of previous caesarean surgery/hysterotomy was present in all patients. Major clinical presentation was cyclical pain. MRI or USG was done and abdominal wall lesions were demonstrated in all cases. Diagnostic laparoscopy was done in 26 of these patients and showed associated endometriosis in 9 patients. Plane of endometriosis was found to be subcutaneous for 9 cases, sheath in 7 and muscular in 12 cases. HPE was proven in all cases. Conclusions: Scar endometriosis is rare. High index of suspicion is needed for diagnosis, especially in cases of previous caesarean sections. MRI and USG are useful tools for diagnosis. Complete wide local excision of scar endometriosis is the primary modality of treatment. Diagnostic laparoscopy along with the procedure is helpful in diagnosing associated pelvic endometriosis.